Charged: how the police try to suppress protest - Foot, Matt (Verso, 2022)
"Since the 1980s, successive British governments, from Thatcher to Johnson, covertly plotted to suppress protest, using standardised aggressive tactics - from batons to horse charges to kettling. Through undisclosed documents and eyewitness accounts; the authors reveal organised police violence against miners at Orgreave, print workers at Warrington, anti-poll tax campaigners, student protestors, and Black Lives Matter activists"--